The ministry of Dr Beyers Naude : towards developing a comprehensive mission (communication) strategy towards the victims of oppression - Niemandt, Cornelius Johannes Petrus (Nelus) (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2010.